Mosaic chromosomal aberrations in synovial fibroblasts of patients with rheumatoid arthritis, osteoarthritis, and other inflammatory joint diseases - Kinne, Raimund W (BioMed Central, 2001)
Chromosomal aberrations were comparatively assessed in nuclei extracted from synovial tissue, primary-culture (P-0) synovial cells, and early-passage synovial fibroblasts (SFB; 98% enrichment; P-1, P-4 [passage 1, passage 4]) from patients with rheumatoid arthritis (RA; n = 21), osteoarthritis (OA; n = 24), and other rheumatic diseases. Peripheral blood lymphocytes (PBL) and skin fibroblasts (FB) (P-1, P-4) from the same patients, as well as SFB from normal joints and patients with joint trauma (JT) (n = 4), were used as controls. Analyses proceeded by standard GTG-banding and interphase centromere fluorescence in situ hybridization. Structural chromosomal aberrations were observed in SFB (P-1 or P-4) from 4 of 21 RA patients (19%), with involvement of chromosome 1 [e.g. del(1)(q12)] in 3 of 4 cases. In 10 of the 21 RA cases (48%), polysomy 7 was observed in P-1 SFB. In addition, aneusomies of chromosomes 4, 6, 8, 9, 12, 18, and Y were present. The percentage of polysomies was increased in P-4. Similar chromosomal aberrations were detected in SFB of OA and spondylarthropathy patients. No aberrations were detected in i) PBL or skin FB from the same patients (except for one OA patient with a karyotype 45,X[10]/46,XX[17] in PBL and variable polysomies in long-term culture skin FB); or ii) synovial tissue and/or P-1 SFB of normal joints or of patients with joint trauma. In conclusion, qualitatively comparable chromosomal aberrations were observed in synovial tissue and early-passage SFB of patients with RA, OA, and other inflammatory joint diseases. Thus, although of possible functional relevance for the pathologic role of SFB in RA, these alterations probably reflect a common response to chronic inflammatory stress in rheumatic diseases.